Comprehensive Support for Academic Teaching: Drawing Inspiration from the Learning Development Model in Higher Education (Discourse of Law and Administration, 2025)
The considerations presented below illustrate the benefits of implementing a comprehensive model of academic teaching and development support in higher education, globally referred to (primarily in Anglo-Saxon countries) as Learning & Development (L&D). This model, originating from the concept of a global approach to employee development management, which is applied in organizations worldwide, has been successfully adapted in the higher education systems of some (so far) countries. It forms a much-desired bridge in academia that connects theory with practice, especially in the context of the ongoing evolution of approaches to education and student competency  development, as well as the growing importance of e-learning, lifelong learning, and the use of new technologies and AI in higher education. Moreover, confronting the pressing issues of our time, some of which threaten the very human existence, undoubtedly requires continuously reshaping effective approaches to teaching methods and strategies in Polish academia. The L&D model, tested in many countries, seems to be an inspiring source of ideas in this regard.
Keywords: Learning Development; academic literacy; higher education; academic writing